Partisipasi Masyarakat Dalam Penyelenggaraan Pemilihan Umum Kepala Daerah - Muhamad Azhar (Administrative Law and Governance Journal, 2018)
This paper aims to find out how the principles of participation in the election of regional heads in Indonesia. The conventional method is an approach that uses a conceptual approach that can be used to analyze synthetic. The results of the study indicate that the basic principles for conducting the election of regional heads must be conducted at the time of openness as a basic principle of community participation. It must also be based on the Principle of Legal Certainty, the orderly principle of the state organizer, the public interest principle. principle of transparency, proportionality principle, principle of professionalism, principles of accountability, principles of efficiency and principle of effectiveness. Keywords: Community Participation, Election of Head of Region, Pricimples of Openness.